Metabolomics of Dry Versus Reanimated Antarctic Lichen-Dominated Endolithic Communities - Fanelli, Giuseppina; Coleine, Claudia; Gevi, Federica; Onofri, Silvano; Selbmann, Laura; Timperio, Anna Maria (Life, 2021)
Cryptoendolithic communities are almost the sole life form in the ice-free areas of the Antarctic desert, encompassing among the most extreme-tolerant organisms known on Earth that still assure ecosystems functioning, regulating nutrient and biogeochemical cycles under conditions accounted as incompatible with active life. If high-throughput sequencing based studies are unravelling prokaryotic and eukaryotic diversity, they are not yet characterized in terms of stress adaptations and responses, despite their paramount ecological importance. In this study, we compared the responses of Antarctic endolithic communities, with special focus on fungi, both under dry conditions (i.e., when dormant), and after reanimation by wetting, light, and optimal temperature (15 °C). We found that several metabolites were differently expressed in reanimated opposite sun exposed communities, suggesting a critical role in their success. In particular, the saccharopine pathway was up-regulated in the north surface, while the spermine/spermidine pathway was significantly down-regulated in the shaded exposed communities. The carnitine-dependent pathway is up-regulated in south-exposed reanimated samples, indicating the preferential involvement of the B-oxidation for the functioning of TCA cycle. The role of these metabolites in the performance of the communities is discussed herein. 6